2016
DOI: 10.1371/journal.pone.0148051
|View full text |Cite
|
Sign up to set email alerts
|

A Familiar(ity) Problem: Assessing the Impact of Prerequisites and Content Familiarity on Student Learning

Abstract: Prerequisites are embedded in most STEM curricula. However, the assumption that the content presented in these courses will improve learning in later courses has not been verified. Because a direct comparison of performance between students with and without required prerequisites is logistically difficult to arrange in a randomized fashion, we developed a novel familiarity scale, and used this to determine whether concepts introduced in a prerequisite course improved student learning in a later course (in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…On the other hand, if the prerequisite course is required before enrolling in the follow-up course, an alternative assessment approach must be taken due to the lack of a control group that has not completed the prerequisite. One method to examine the impact of prerequisites in this scenario is by assessing student performance on exam questions in the follow-up course that are based on the level of familiarity one has with the tested content from the prerequisite course (Shaffer et al 2016, Sato et al 2017. In this analysis, exam questions are coded (by instructors, students, or lecture slide analysis) as "very familiar" if the topic was previously covered extensively in the prerequisite, "familiar" if the topic was briefly introduced in the prerequisite course, and "not familiar" if the topic was not taught at all in the prerequisite course.…”
Section: Continued On Next Pagementioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, if the prerequisite course is required before enrolling in the follow-up course, an alternative assessment approach must be taken due to the lack of a control group that has not completed the prerequisite. One method to examine the impact of prerequisites in this scenario is by assessing student performance on exam questions in the follow-up course that are based on the level of familiarity one has with the tested content from the prerequisite course (Shaffer et al 2016, Sato et al 2017. In this analysis, exam questions are coded (by instructors, students, or lecture slide analysis) as "very familiar" if the topic was previously covered extensively in the prerequisite, "familiar" if the topic was briefly introduced in the prerequisite course, and "not familiar" if the topic was not taught at all in the prerequisite course.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…In this analysis, exam questions are coded (by instructors, students, or lecture slide analysis) as "very familiar" if the topic was previously covered extensively in the prerequisite, "familiar" if the topic was briefly introduced in the prerequisite course, and "not familiar" if the topic was not taught at all in the prerequisite course. Shaffer et al (2016) examined the impact of a genetics prerequisite on performance in a molecular biology course and a human physiology prerequisite on performance in a human anatomy course. This study (Shaffer et al 2016) demonstrated limited differences on performance among questions of varying familiarity, suggesting that students did not necessarily utilize or need their prerequisite knowledge in follow-up courses.…”
Section: Continued On Next Pagementioning
confidence: 99%
See 2 more Smart Citations
“…By association, it is emphasized that learning through familiar means will also provide the resources needed to assimilate different means, and preferences will in most cases be those with which the learner is familiar (Shaffer, et al, 2016).…”
Section: Governing Concepts Of the Modelmentioning
confidence: 99%